2008
DOI: 10.1016/j.neuroimage.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated responses in the amygdala and orbitofrontal cortex to bottom–up and top–down components of emotional evaluation

Abstract: Although emotional responses to stimuli may be automatic, explicit evaluation of emotion is a voluntary act. These bottom-up and top-down processes may be supported by distinct neural systems. Previous studies reported bottom-up responses in the amygdala, top-down responses in the orbital and ventromedial prefrontal cortices, and top-down modulation of the amygdalar response. The current study used event-related fMRI on fifteen healthy males to examine these responses in the absence of stimulus anticipation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 50 publications
1
42
1
Order By: Relevance
“…A number of studies have consistently suggested the important role of PCu/PCC activity in these emotion-related cognitive processes, including emotion evaluation (Wright et al, 2008), happy and sad word processing (Maddock et al, 2003), and social behavior (Adolphs, 2003). Several studies have also shown that individuals with greater PCu/PCC activation might be able to resolve depressive moods more easily (Mayberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have consistently suggested the important role of PCu/PCC activity in these emotion-related cognitive processes, including emotion evaluation (Wright et al, 2008), happy and sad word processing (Maddock et al, 2003), and social behavior (Adolphs, 2003). Several studies have also shown that individuals with greater PCu/PCC activation might be able to resolve depressive moods more easily (Mayberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Orbitofrontal cortex and hippocampal regions, which were uniquely active during phobic fear, might underlie the conditioned avoidance characteristic of phobic, but not normative fear. OFC has been implicated in conditioning paradigms, specifically signaling the reinforcement value of stimuli (Phelps et al, 2004) in a top-down manner (Wright et al, 2008), while hippocampal regions trigger contextual memory of threat (Milad et al, 2007). Together, these regions may serve to maintain the phobia by recalling previous episodes of fear and associating the snake with a fearful response.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of schizophrenia on fMRI responses in the amygdala and hippocampus was largely linked with current medication status, thus confirming previous reports (Rasetti et al 2009), but the effect on the PFC and ACC was independent of it. The amygdala activates with bottom-up, stimulusdriven emotional processing (Wright et al 2008), and neural responses in the amygdala correlate with the subjective experience of emotion (Liberzon et al 2000 ;Taylor et al 2003). Conversely, the PFC and ACC exert an inhibitory feedback on the amygdala in response to aversive stimuli (Pezawas et al 2005).…”
Section: Discussionmentioning
confidence: 99%